Diagnostic performance of coronary CT angiography carried out with a novel whole-heart coverage high-definition CT scanner in patients with high heart rate. (15th April 2018) - Andreini, Daniele; Mushtaq, Saima; Pontone, Gianluca; Conte, Edoardo; Guglielmo, Marco; Annoni, Andrea; Baggiano, Andrea; Formenti, Alberto; Ditali, Valentina; Mancini, Maria Elisabetta; Zanchi, Simone; Melotti, Eleonora; et al.
Abstract: Background: Aim of the study was to evaluate image quality, radiation exposure and diagnostic accuracy of coronary CT angiography (CCTA) performed with a novel cardiac CT scanner in patients with very high heart rate (HR). Methods: We prospectively enrolled 202 patients (111 men, mean age 66 ± 8 years) with suspected coronary artery disease who underwent CCTA with a whole-organ volumetric CT scanner. The HR during the scan was ≥ 80 bpm in 100 patients (Group 1), while it was ≤ 65 bpm in the remaining 102 patients (Group 2). In all patients, image quality score and coronary interpretability were evaluated and effective dose (ED) was recorded. In 86 of the 202 enrolled patients (40 patients in Group 1, 46 patients in Group 2) who were referred for a clinically indicated invasive coronary angiography (ICA) within 6 months, diagnostic accuracy of CCTA vs. ICA was evaluated. Results: Mean image quality and coronary interpretability were very high in both Groups (Likert = 3.35 vs. 3.39 and 97.3% [1542/1584 segments] and 98% [1569/1600 segments] in Group 1 and Group 2, respectively). Mean ED was lower in Group 2 (1.1 ± 0.5 mSv) compared to Group 1 (2.9 ± 1.6 mSv). In Group 1, sensitivity and specificity of CCTA for detection of > 50% stenosis vs. ICA were 95.2% and 98.9% in a segment-based analysis and 100% and 81.8% in a patient-based analysis, respectively. Conclusions: The whole organ high-definition CT scanner allows evaluating coronary arteries in patients with high HR with excellent image quality, coronary interpretability and low radiation exposure.